Dilemmas in Teaching Happiness - Barker, Chris; Martin, Brian (Journal of University Teaching and Learning Practice, 2009)
There is a burgeoning amount of research into happiness and greatly increased popular attention, so it seems logical to add a course on happiness to the university curriculum. We encountered, in developing and running such a course, a number of dilemmas that the topic of happiness makes especially acute. Should the teacher remain separate from the class, as an authority, or participate in group activities? Is the primary goal of the class to learn content or to change the relationship of students to the world? What does a mark for learning content signify if developing happiness habits is a goal? Should one goal of the class be for the teacher to be happy and, if so, does this conflict with student learning? These dilemmas reflect larger questions about the purpose of university education. This paper reflects on those questions through our experience of formulating and delivering a new university class on happiness.